OP0251 Attainment of low disease activity and remission in systemic lupus erythematosus patients with high disease activity in the atacicept phase iib address ii study and its long-term extension. (12th June 2018) - Morand, E.; Merrill, J.T.; Isenberg, D.A.; Kao, A.H.; Vazquez–Mateo, C.; Wax, S.; Chang, P.; Pudota, K.; Aranow, C.; Wallace, D.
Abstract : Background: Low disease activity (LDA) and remission are consummate goals of SLE treatment. 1 Lupus Low Disease Activity State (LLDAS) is associated with reduced damage accrual, 2 and has been shown to be a feasible clinical trial endpoint. 3 In the Phase IIb ADDRESS II study, 4 atacicept improved SRI-6 response rates and flare prevention at Week (Wk) 24 vs placebo (PBO), in patients with High Disease Activity (HDA; SLEDAI-2K≥10) at Screening, with an acceptable safety profile. Objectives: Post-hoc analysis of ADDRESS II and its long-term extension to describe 48-wk rates of LDA and remission in patients with HDA at Screening. Methods: Pts were randomised 1:1:1 to weekly subcutaneous PBO or atacicept 75 or 150 mg for 24 wks in ADDRESS II. Completers entered the extension study at the same dose, except PBO patients who switched to atacicept 150 mg (PBO/atacicept 150 mg). This analysis includes: LDA (SLEDAI-2K≤2); LLDAS (SLEDAI–2K≤4 without major organ activity, no new disease activity vs previous visit, Physician's Global Assessment [PGA]≤1, prednisone-equivalent ≤7.5 mg/day, and stable immunosuppressants); and remission (clinical SLEDAI-2K=0, PGA <0.5, prednisone ≤5 mg/day) per definitions proposed by DORIS. 1 Results: Of 306 ADDRESS II pts, 158 (52%) had HDA at entry; 42.4% achieved SRI-6, 23.4% LDA, 15.8% LLDAS and 10.8% remission at Wk 24. At Wk 48, 52.5% achieved SRI-6, 26.6% LDA, 19.0% LLDAS and 10.8% remission. Among the 83 HDA patients with an SRI-6 response at Wk 48, LDA, LLDAS, and remission represented increasingly stringent subsets (49.4% [n=41] attaining LDA, 34.9% [n=29] LLDAS, and 20.5% [n=17] remission). LDA, LLDAS and remission rates were higher in patients treated with atacicept 150 mg vs 75 mg and PBO/atacicept 150 mg (table 1; figure 1). Conclusions: At 48 wks, patients entering the ADDRESS II study with HDA who received atacicept 150 mg were more likely to attain LDA, LLDAS and remission than those treated with 75 mg or PBO/atacicept 150 mg. These endpoints were more stringent and discriminatory than SRI-6, confirming LLDAS, LDA, and remission to be robust and meaningful endpoints for SLE trials, and adding further support for future studies of atacicept in SLE. References: [1] Van Vollenhoven, et al. Ann Rheum Dis2017. [2] Franklyn, et al. Ann Rheum Dis2016. [3] Morand, et al. Ann Rheum Dis2018 (in press). [4] Merrill, et al. Arthritis Rheum2017. Disclosure of Interest: E. Morand Grant/research support from: AstraZeneca/Medimmune, Janssen, UCB and BMS, Consultant for: EMD Serono, AstraZeneca/Medimmune, and Janssen, J. T. Merrill Grant/research support from: GSK and BMS (investigator-initiated studies), Consultant for: EMD Serono, Lilly, GSK, Anthera and Biogen; Clinical Trial Data Management/Analysis/QA Services for Celgene and Xencor, D. A. Isenberg Consultant for: EMD Serono (consulting fees have been passed to a local arthritis charity), A. H. Kao Employee of: EMD Serono Research and Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), C. Vazquez–Mateo Employee of: EMD Serono Research and Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), S. Wax Employee of: EMD Serono Research and Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), P. Chang Employee of: EMD Serono Research and Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), K. Pudota Employee of: EMD Serono Research and Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), C. Aranow Grant/research support from: EMD Serono Research and Development Institute, Inc., D. Wallace Consultant for: Merck KGaA